Coral mortality discrimination and habitat phase shift analysis using landsat TM and ETM+ imageries of Balabac, Palawan - Abella, Margaux Angelica R. (2007)
This study aimed to address the problem of discriminating not only among general benthic cover classes but also between coral mortality states using image classification. More importantly patterns in phase shifts of coral reef environments were studied using post-classification change detection and spatial analysis to determine which directions of change were most prevalent in the study areas, at what exact locations they occurred, and what factors may have contributed to the change.
Maximum likehood classification was used to classify the 1988-1989 and 1999-1999 image mosaics into live coral, dead coral, rubble, sand, seagrass, and short seagrass, yielding overall accuracies of 71.61% and 78.59%, respectively. It was evident from the results of the post-classification change detection that coral and mangroves have undergone significant degradation and about 18% of the entire area underwent negative phase shift. Overall, the islands of Tangkahan, Pulao Bato, and Unok have been determined to be change hotspots, based on the comparison of percentages of negative and positive changes. All islands except the southern tip of Palawan mainland have been identified as mangrove hotspots, and Bancalaan, Malinsono, Pandanan, Patonggong, Pulao Bato, Tangkahan, and Unok were identified as coral hotspots. Among the correlations performed, the analysis between the type of threat and type of negative change yielded the most realistic and informative results.
With the outputs from this study, concerned parties or individuals would know where immediate action is needed. Furthermore, if there is a time series of this type of information, the rate and trend of degradation may be analyzed to come up with more effective solutions to the problem and timely mitigation measures. With the availability of more detailed, accurate, and complete data, a better correlation between the identified hotspots in this study and possible change factors may be possible.
Thesis (M.S. Remote Sensing)--University of the Philippines, Diliman.
Keywords: Coral reefs and islands -- Remote sensing. -- Philippines -- Balabac (Palawan); Benthos -- Habitat -- Remote sensing. -- Philippines -- Balabac (Palawan)